Barriers to Puberty Talk between Mothers and Daughters: A Qualitative Study - Mirzaee, Firoozeh; Pouredalati, Malihe; Ahmadi, Atefeh; Ghazaznfarpour, Masumeh (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The aim of the present study is to explain the barriers to puberty talk between mothers and daughters.Methods In the present study, the conventional content analysis method was used. The present study was conducted from September 2018 to August 2019 in Iran. The study population consisted of mothers and adolescent girls. The data was collected using purposeful sampling method. The sample consisted of 4 mothers and 6 girls that were interviewed using semistructured interviews. Data collection continued until data saturation was achieved. Data analysis was conducted as described by Graneheim et al. using NVivo 11 software.Results In the present study, after exploring the views of the participants about barriers to puberty talk between mothers and daughters, one dominant theme emerged. Puberty talk is seen as an “inappropriate talk with a girl.” There were several subthemes, including “lack of mother's awareness regarding the school role, the busy schedule of the mother, and the adoption of alternatives to mother's talk with girls”.Conclusions Different sociocultural factors affect puberty talk between mothers and adolescent girls. It is important that mothers and policy makers take these barriers into account.
Keywords: content analysis; puberty; girls; mothers; qualitative study